STRATEGIC PRIORITIES FOR MODERNIZING THE TRANSPORT AND LOGISTICS INFRASTRUCTURE OF UZBEKISTAN - Abdurakhmanova Mukaddas Tokhtasinovna (Ecomind Press, 2026)
This research analyzes the current condition and future development prospects of the transport and logistics sector in the Republic of Uzbekistan. The study explores initiatives aimed at upgrading the nation’s transport infrastructure, enhancing logistics operations, strengthening participation in international transport corridors, and addressing key challenges associated with the sustainable advancement of the industry. Particular emphasis is placed on evaluating the sector’s contribution to national economic performance, its role in boosting the country's competitiveness, and its impact on improving societal welfare.
Keywords: Transport and logistics system, infrastructure modernization, logistics operations, international transport corridors, sustainable sectoral development, economic advancement, national competitiveness.